2020
DOI: 10.1007/s43032-019-00095-4
|View full text |Cite|
|
Sign up to set email alerts
|

Nicotine Suppresses the Invasiveness of Human Trophoblasts by Downregulation of CXCL12 Expression through the Alpha-7 Subunit of the Nicotinic Acetylcholine Receptor

Abstract: Smoke exposure during pregnancy has detrimental effects upon numerous fetal and neonatal outcomes. Nicotine (the main component of tobacco) has been suggested to affect placental development. During placental development, efficient invasion by trophoblasts is required for establishment of the fetus-maternal circulation. In this study we explored the regulation of trophoblast invasion by nicotine. An immortalized first trimester extravillous trophoblast cell line (HTR-8/SVneo cells) was used for all the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…In this study we used the in vivo worst-case scenario concentrations of nicotine (15 µM) and ethanol (2‰) that were not causing placental explant cell death according to LDH release (data not shown). Chen et al (2020) used several nicotine concentrations (0.1–10 µM) at three time points, that did not cause cell death in HTR-8/SVneo cells supporting our viability results. However, a two times higher concentration of ethanol (4 mg/ml), compared to the one used in this study (2‰ that equals to 2 mg/ml), has been shown to cause cell death in HTR-8/SVneo cells at 48 h ( Shanmugam et al, 2019 ).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In this study we used the in vivo worst-case scenario concentrations of nicotine (15 µM) and ethanol (2‰) that were not causing placental explant cell death according to LDH release (data not shown). Chen et al (2020) used several nicotine concentrations (0.1–10 µM) at three time points, that did not cause cell death in HTR-8/SVneo cells supporting our viability results. However, a two times higher concentration of ethanol (4 mg/ml), compared to the one used in this study (2‰ that equals to 2 mg/ml), has been shown to cause cell death in HTR-8/SVneo cells at 48 h ( Shanmugam et al, 2019 ).…”
Section: Resultssupporting
confidence: 82%
“…3 ). Interestingly, Chen et al (2020) have shown that immortalized first trimester extravillous trophoblast (HTR-8/SVneo) cells also express nAChRα7 both at mRNA and protein level.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Other chemicals within cigarettes may also act though upon the placenta. The placenta expresses nicotinic acetylcholine receptor (nAChR) subunits that regulate TB cell invasion but whose expression and signaling pathway can be usurped by nicotine contained within tobacco smoke (Lips et al, 2005;Machaalani et al, 2014Machaalani et al, , 2018Aishah et al, 2017;Chen et al, 2020). For instance, nicotine acting through nAChR induced endoplasmic reticulum stress in rat pTGC (Wong et al, 2016).…”
Section: Smokingmentioning
confidence: 99%
“…In this work, we also conducted an iTRAQbased quantitative proteomic analysis, and the data reveals that 295 proteins were downregulated and 305 proteins were upregulated in OGD-ECs compared to normal control ECs (data not shown). It was known that several factors such as IL-17, HIF-1α, E2, and FGF-2 could regulate the expression of CXCL12 [36][37][38][39], and we are performing an in-depth study for the mechanisms of CXCL12 increase in EPCs in another study. EPCs-CM or EPC transplantation improves the white matter integrity, decreases capillary breakdown, and inhibits apoptosis after traumatic brain injury (TBI) [12,40].…”
Section: Discussionmentioning
confidence: 99%